Tourism Transition and Green Economy: Inspire or Prevent People's income in the Covid-19 Shock - Heni Noviarita; Muhammad Kurniawan; Khavid Normasyhuri; Gustika Nurmalia (Faculty of Economics and Business Udayana University, 2023)
This research was conducted with the aim of analyzing the green economy transition in tourism, especially tourist villages, whether it is able to provide inspiration or actually prevent an increase in people's income in conditions of the COVID-19 shock. The research was carried out in tourist villages in West Java and Lampung Provinces. This study found thatthe transition of a tourist village with the concept of green economy has a strong influence in increasing the income of rural tourism communities in conditions of the COVID-19 shock, this is due to the fact that the green economy concept encourages the utilization of natural resources and environmental preservation, this will ensure a sustainable attraction for tourists which in turn can increase revenue. Keywords: COVID-19; green economy; tourism village.